Preaching on the revised common lectionary for the feast of Christ the King: Joy for intuitive thinking types, nightmare for sensing feeling types? - Francis, Leslie J. (HTS teologiese studies, 2021)
This qualitative study was positioned within an emerging scientific field concerned with the interaction between biblical text and the psychological profile of the preacher. The theoretical framework was provided by the sensing, intuition, feeling and thinking (SIFT) approach to biblical hermeneutics, an approach rooted in reader-perspective hermeneutical theory and in Jungian psychological type theory that explores the distinctive readings of sensing perception and intuitive perception, and the distinctive readings of thinking evaluation and feeling evaluation. The empirical methodology was provided by developing a research tradition concerned with applying the SIFT approach to biblical text. In the present study, a group of 17 Anglican clergy were invited to work in psychological type-alike groups to explore two of the biblical passages identified by Year B of the Revised Common Lectionary for the Feast of Christ the King. Dividing into three workshops, according to their preferences for sensing and intuition, the clergy explored Psalm 93. Dividing into three workshops, according to their preferences for thinking and feeling, the clergy explored John 18:33–37. The rich data gathered from these workshops supported the hypothesis that biblical interpretation and preaching may be shaped by the reader’s psychological type preference and suggested that the passages of scripture proposed for the Feast of Christ the King may be a joy for intuitive thinking types, but a nightmare for sensing feeling types.Contribution: Situated within the reader perspective approach to biblical hermeneutics, the SIFT method is concerned with identifying the influence of the psychological type of the reader in shaping the interpretation of text. Employing this method, the present study contributes to the fields of homiletics and hermeneutics by demonstrating how some readers (sensing types) may struggle more than others (intuitive types) to interpret the scripture readings proposed by the lectionary for the Feast of Christ the King.